Communicative Competence in an Online Teacher Community: An Ethnographic Study - Nahida Akter Poly (Association of Language Teachers in Southeast Asia (ALTSA), 2026)
This study seeks to examine how teachers and education professionals communicate through memes and comments in an online Facebook teacher community. Using a qualitative digital ethnographic approach, the study analyses more than 25 highly interactive meme posts and their associated comment threads collected over a four-week observation period. The data were documented through screenshots and analysed qualitatively without direct participant interaction, as all materials were publicly accessible. The research employed Hymes’s SPEAKING framework as an analytical tool to explore how linguistic and semiotic choices reflect shared norms, roles, and cultural expectations within the online community. The findings reveal that meme-based communication is characterised by informal and abbreviated language, professional jargon, and deliberate nonstandard forms such as LOLspeak. Humour, expressed through irony, hyperbole, and exaggeration, serves as both a coping mechanism for professional stress and a marker of solidarity among community members. These multimodal practices support tone management, community bonding, and critical commentary while maintaining socially appropriate interaction. The study concludes that memes and comments function as meaningful communicative resources through which teachers enact communicative competence in digitally mediated environments. The findings underscore the significance of digital ethnography in elucidating language use, professional identity, and social meaning within online teacher communities.